future scenario of Brexit: position of Scottish nationalists - Okhoshin Oleg (Научно-аналитический вестник Института Европы РАН, 2018)
In the summer of 2018, serious changes took place in British politics. The issue of Britain’s withdrawal from the European Union even more divided Conservative Party. After lengthy debate, Theresa May’s government outlined the general position on Brexit in the White Paper. There are still controversial points in it, which aroused sharp criticism of supporters of a «hard» EU divorce and led to the resignation of two ministers – D. Davis and B. Johnson. In Scotland, the local government requires certainty from T. May and wants to know what line the UK will take in negotiations with the European Union in case of «no deal». In this situation, T. May tries to take a cautious stance promising Scotland subsidies in order to save the loyalty of the region to the UK